2022
DOI: 10.1038/s41598-022-15263-x
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-143-3p inhibits Wnt-β-catenin and MAPK signaling in human corneal epithelial stem cells

Abstract: Our previous study demonstrated hsa-miR-143-3p as one of the highly expressed miRNAs in enriched corneal epithelial stem cells (CESCs). Hence this study aims to elucidate the regulatory role of hsa-miR-143-3p in the maintenance of stemness in CESCs. The target genes of hsa-miR-143-3p were predicted and subjected to pathway analysis to select the targets for functional studies. Primary cultured limbal epithelial cells were transfected with hsa-miR-143-3p mimic, inhibitor or scrambled sequence using Lipofectamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In addition, the miR-143-3p inhibited osteogenic differentiation in dental pulp stem cells by binding to TNF-α via inactivating the NF-κB signaling pathway [21]. Interestingly, the miR-143-3p facilitated self-renewal and enhanced the expression of pluripotency genes in mouse embryonic stem cells, which revealed that hsa-miR-143-3p could maintain the stemness in corneal epithelial stem cells (CESCs) [22]. MiR-143-3p also suppressed glycolysis mentalism and reduced tumor formation via targeting HK2 [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the miR-143-3p inhibited osteogenic differentiation in dental pulp stem cells by binding to TNF-α via inactivating the NF-κB signaling pathway [21]. Interestingly, the miR-143-3p facilitated self-renewal and enhanced the expression of pluripotency genes in mouse embryonic stem cells, which revealed that hsa-miR-143-3p could maintain the stemness in corneal epithelial stem cells (CESCs) [22]. MiR-143-3p also suppressed glycolysis mentalism and reduced tumor formation via targeting HK2 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, some of the miRNAs highlighted in our study are strong candidates for functional follow-up. For instance, hsa-miR-143-3p—which affects neutrophil counts mediated by BCL2 expression—has been implicated in numerous immunological diseases such as cancers and ischemic stroke [ 48 - 50 ], has been found to influence inflammatory factors and cell apoptosis [ 51 , 52 ], and to inhibit Wnt and MAPK signaling [ 53 ]. Similarly, hsa-miR-199b, which influences neutrophils through ETS1 expression, has previously been implicated in breast cancer [ 54 , 55 ], and described as a tumor suppressor in acute myeloid leukemia [ 56 ] and an inducer of apoptosis in oral cancer [ 51 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were inoculated into a 6-well plate and transfected with control and Drp1 overexpressed plasmids. All transfections were performed using Lipofectamine 3000 (L3000008, Invitrogen, USA) according to the manufacturer’s instructions [ 30 ]. Transfection efficiency was confirmed by western blot.…”
Section: Methodsmentioning
confidence: 99%